Demographic profile of patient with acute watery diarrhea during monsoon 2022: Patan Hospital, Nepal - Joshi, Sneha; Baniya, Shreya; Shrestha, Ashis; Bajracharya, Sumana; Rajbhandari, Piyush; Joshi, Sushmita (Journal of Patan Academy of Health Sciences, 2023)
Introduction: Diarrhea is the passage of three or more loose or liquid stools per day or more. Acute watery diarrhea is a major public health problem worldwide.  In Nepal, diarrhea is among the top 10 inpatient morbidity. This study’s objective is to monitor demographic characteristics and laboratory findings of stool specimens of diarrhea.Method: This is a cross-sectional descriptive study done at Patan Hospital. Ethical approval was taken from the Ethical committee. Data for Monsoon 2022 (June to September 2022) were collected from the Patan Hospital record system. Cases from within the Lalitpur district were included.Result: Out of 119 cases, 50(42%) were male and 69(58%) were female. The mean age±SD was 33.28±25.38 (p=0.083) with maximum cases observed during June and a peak observed during the fourth week of June. Out of 119, 4(3.3%) were stool culture positive. Two cases of Vibrio cholera, one case of Shigella sonnei, and one case of Salmonella parathypi B were isolated. In the etiological profile, 14 Entamoeba histolytica were isolated.Conclusion: During the outbreak of diarrhea in Monsoon 2022, adults were affected most. The culture of acute watery diarrhea showed two cases of Vibrio cholera.